'A new type of revolution': socialist thought in India, 1940s–1960s. Issue 4 (2nd October 2018) - Sherman, Taylor C.
ABSTRACT: Although it is often said that early postcolonial India was socialist, scholars have tended to take this term for granted. This article investigates how Indians defined socialism in the two decades after independence. It finds that there were six areas of agreement among Indian socialists: the centrality of the individual, the indispensability of work, the continued importance of private property, that the final goal was a more equal – but not flat – society, that this change had to be brought about without violence, and that the final goal of Indian socialism ought to be spiritual fulfilment. Understanding how Indians defined their version of socialism, it is argued, will help scholars re-evaluate the role of the first prime minister, Jawaharlal Nehru, in defining the goals India pursued after independence. It will also re-orient our understanding of the expectations and limitations of the Indian state in this crucial period in Indian history.